BASIC MATHEMATICAL FORM OF MICHELL STRUCTURE - Khushak, Sanaullah; Luo, Ani; Basit Chandio, Muhammad; Raza, Asif (Journal of Applied Engineering Science, 2021)
Michelle structure is well known due to its optimization form & minimum mass of the structure. The idea has been adopted by James C Maxwell’s result on truss design. In this paper, we have presented the simple mathematical model of Michelle structure for the basic complexity order q=2 in the two-dimensional coordinate system. This mathematical model based on the construction of a structure that includes the analysis coordinate of all Nodes, and all member location of the structure along with analysis of their Connectivity matrices; these parameters form a whole tensegrity system of Michelle structure. The force density in each member of the structure has been investigated on every single node of structure individually. The mathematical form of structure has been developed in this research, which can be helpful to develop the high order complexity structure by applying the same methodology. The selection of bars and string has been carried out in a simple way. Moreover, the expression for calculating the minimum mass of structure has been defined at the end of this paper, which is the most important factor for constructing any kind of tensegrity structure.
Keywords: force density; mathematical form; Michell structure; minimal mass; tensegrity structure